Pengaruh Kepemimpinan Transformasional Terhadap Kesiapan untuk Berubah di Mediasi Motivasi Kerja dan Komitmen Organisasional pada Dinas Kependudukan dan Pencatatan Sipil di Indonesia - Pratama, Reza Hardian; Khotimah, Ayyumi Khusnul (Multidisciplinary Journal of Education , Economic and Culture, 2024)
This study aims to determine transformational leadership on work motivation, transformational leadership on organizational commitment, work motivation on readiness to change, organizational commitment on readiness to change, organizational commitment on work motivation, transformational leadership on readiness to change, transformational leadership through work motivation on readiness to change, transformational leadership through organizational commitment on readiness to change. The purposive random sampling method, this study uses the SEM-PLS analysis tool with a sample of 387. The results of this study are transformational leadership has a positive and significant effect on organizational commitment. Transformational leadership has a positive and significant effect on work motivation. Organizational commitment has a positive and significant effect on readiness to change. Work motivation has a positive and significant effect on readiness to change. Transformational leadership has a positive and significant effect on readiness to change. Work motivation has a positive and significant effect on organizational commitment. Transformational leadership through work motivation has a positive and significant effect on readiness to change